MORPHOLOGICAL AND LECTIN HISTOCHEMICAL FEATURES OF WHITE NONLINEAR RATS MYOCARDIUM DURING EXPERIMENTAL HYPOTHYROIDISM - Yashchenko, A.; Smolkova, O. (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
General morphology and glycoconjugates of myocardium structural components has been studied in control and experimental animals. Experiments were performed on mature rats - males with weight 150-180g, who were divided into two groups (10 control and 10 experimental). Exogenous ypothyroidism was induced by daily administration of food thyreostatic drug mercazolilum at a dose of 7 mg / kg body weight within 30 days. After 30 days the animal euthanasia was performed by an overdose of ether anesthesia. Histological material (pieces of myocardium from ventricular areas and thyroid gland) were fixed in 4% neutral formalin, dehydrated, compacted and embedded in paraffin. Sections 5-7 μm thick were stained by hematoxylin and eosin for general morphology. Glycoconjugate carbohydrate determinants of myocardium structural components were studied by lectin-peroxidase technique using LABA (LFuc), HPA (NAcDGal), WGA (DGlcNAc>NeuNAc) lectins. Function control of thyroid gland was performed by investigation of thyroid glands morphology after staining slides by hematoxylin and eosin, and by determining T3 and T4 hormones in blood serum using radiological method by means of standard sets. It is shown that in hypothyroidism hypechromia of cardiomyocytes’ nuclei, expansion of myocardial vascular lumen, perivascular edema and insignificant interstitial infiltration by leukocytes, local area accumulations of adipocytes are observed. Based on lectin histochemical studies it is shown modification of lectin receptors in the nuclei of cardiomyocytes and in endothelial cells of the microcirculatory bed, thus indicating the change of intensity of metabolic processes in cardiac myocytes and endothelial cells of the microcirculatory bed on the background of experimental hypothyroidism. DGlcNAc> NeuNAc-specific WGA lectin may be a marker of endothelial cells.